Evaluación de la capacidad antioxidante in vitro de los extractos etanólicos de flavonoides totales de brotes de solanum tuberosum sp. papa negra - Altamirano Sarmiento, José Luis (2016)
This study aimed to evaluate the antioxidant capacity in vitro of the ethanolic extracts of total flavonoids of outbreaks of Solanum tuberosum sp. "black potato". The method Kostennikova Brand Z and Williams et al were used, who were adapted to laboratory conditions of phytochemistry Natural Products and Faculty of Chemical Engineering. The raw material (black potato) was divided and saved into four lots, the evaluation the stages of shoot growth of the black potato was done to 30, 40, 50 and 60 days. The study material of the first batch (black potato buds) was collected at 30 days; dried, ground and sieved to a diameter of 212 microns; sieving was stored in a glass jar amber; This same process is repeated for all lots. With the screening was prepared saved 250 mL final fluid extract; quantification of total flavonoids extract fluid outbreaks black pope was performed by UV- visible spectrophotometry. Antioxidant capacity in vitro of total flavonoids obtained black potato sprouts was determined using the method described by Brand Williams et al. It was observed that the total concentration of flavonoids in potato sprouts black is time dependent outbreak, obtaining a higher concentration of total flavonoids at 40 and 50 days. The results of the evaluation of the antioxidant activity kidnapping of radical (DPPH) indicate that flavonoids obtained from outbreaks of 40 days reported the highest rate of capture of free radical, 49.06 ± 0.51%